ANALISIS PENGARUH TRANSAKSI GADAI EMAS TERHADAP TINGKAT KEUNTUNGAN BANK SYARIAH - Kurniawati, Eris Tri (Journal of Innovation in Business and Economics, 2013)
The basis of this study was to provide a comprehensible description of the gold pawn transaction implemented in sharia banks and would like to identify the effect of the gold pawn transactions toward bank profits. Accordingly, this research applied statistical test instrument, specifically multiple linear regressions and the results revealed that sharia (Rahn) pawn transaction revenue has a positive effect on net income in which the contribution of independent variables on the dependent variable indicated its R2 (R-squared)value by 21.08%. Since the independent variable was not the major product which affected the bank's net income, other 78.92% of net profit variable would be clarified by other variables which were not discussed in this study